Sanity & Tallulah. Shortcuts - Brooks, Molly (Molly Grayson) (Little, Brown and Company, 2021)
When most of the adults on space station Wilnick come down with the flu, best friends Sanity and Tallulah are tasked with delivering items to another station, but when they take a shortcut, they accidentally end up on the other side of the military blockade.